HUBUNGAN TINGKAT PENGETAHUAN KELUARGA TERHADAP SIKAP KELUARGA DALAM PEMBERIAN PERAWATAN ACTIVITIES DAILY LIVING (ADL) PADA LANSIA DI RUMAH DI DESA TANJUNGREJO MARGOYOSO PATI - Narayani, Icca; Kartinah, Kartinah (Universitas Muhammadiyah Surakarta, 2009)
The various problems of health faced by old age are immobilizes, dementia, incontinence, less food and beverage, chafed and decubitus, broken bone and others (Siburian, 2005). Family played important part in treatment of old age. Take care of old age is not a easy work because this matter need knowledge, skilled, willingness, patience and devotion (Siburian, 2005). Target of this research is to know correlation between storey; level knowledge of family to family attitude in giving of treatment of Activity of Daily Living (ADL) at lansia at home countryside of Tanjungrejo Margoyoso Pati. The research is carried out in Tanjungrejo Village of Margoyoso district of Pati Regency. The research population are all family’s there are have the old age in their house. The research sample are 96 family have past of inclusion and exclusion criteria of research. The collecting data uses questionnaire and observation methods. The gathered data are analyzed with statistic of bevariate technique namely rank spearman. The conclusion of this research is (1) the family knowledge about ADL for the old age are good enough, (2) the family attitude in gives ADL care to old age are positive, and (3) there are correlation between family knowledge about ADL and family attitude in gives ADL care to old age in Tanjungrejo Village of Margoyoso district of Pati Regency.